A Panel Study of Immigrants' Overeducation and Earnings in Australia - Le Wen; Sholeh A. Maani (Institute of Labor Economics (IZA), 2017)
The recent literature on overeducation has provided divergent results on whether or not overeducation bears an earnings penalty. In addition, few studies have considered overeducation among immigrants. This paper uses panel data analyses to investigate the match between education and occupation and resulting earnings effects for immigrants from English Speaking, and Non-English Speaking, Backgrounds relative to the native-born population in Australia. Based on nine years of longitudinal data, the panel approach addresses individual heterogeneity effects (motivation, ability, and compensating differentials) that are crucial in overeducation analysis. First, we find that immigrants have significantly higher incidence rates of overeducation than the native-born. This probability increases, rather than diminishes, once we control for unobserved correlated effects. Second, based on panel fixed effects analyses there is no penalty for overeducation for ESB immigrants. However, NESB immigrants receive a lower return to required and overeducation compared to the other groups after controlling for individual heterogeneity.
Keywords: J24; J15; J31; 330; over-education; educational mismatch; immigrants; non-English-speaking; panel data; wage effects